Smart pulse oximeter systems for spo2 measurement based on IOT - Hema, L. K.; Priya, R. Mohana; Kumar Dwibedi, Rajat; Vijay, J (International Journal of Psychosocial Rehabilitation, 2020)
For a patient with arrhythmia, a surveillance and warning device, particularly during the night of rest, can reduce the risk of death from heart attacks. A public pulse oximeter attached to the Internet of Things (IoT) system enables a family member to monitor a patient remotely. It is critical to provide an actual-time alert system capable of alert a patient when they are at danger. The unit uses a pulse oximeter module, a WLAN router to link the device to the cloud server, which is capable of displaying data on the Android display. Equipment for the patient is powered by a generator. Battery power is monitored, too. The heart rate's lowest reading accuracy was 96.9 per cent (normal, bradycardia and tachycardia) compared to the fingertip pulse oximeter's measured efficiency. Remote control data transmission speed depends on Internet access capacity.